What is Crossplane? - Cope, Nic (O'Reilly Media, Inc., 2023)
Control planes provide an increasingly popular approach to orchestrating an organization's cloud infrastructure and applications. Crossplane, a low-code Kubernetes-based framework, takes you a step further. While cloud control planes generally have backends that orchestrate the data plane and frontends that expose an API, Crossplane takes the Kubernetes control plane and makes both its backend and frontend highly extensible. In this report, author Nic Cope explains how Crossplane's backend empowers developers to safely and efficiently build a control plane to orchestrate any application or infrastructure. With Crossplane, you can extend the backend to control any kind of system and extend the frontend APIs to expose whatever concepts make sense for your organization.